Strategic vigilance and its impact on achieving organizational excellence: Analytical research at the Al-Qaim Cement Plant. (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to identify the role of strategic vigilance as an independent variable in organizational excellence as a dependent variable in the Al-Qaim Cement Factory. The descriptive analytical approach was based upon the current research, and try to come up with a set of recommendations that work to enhance the practice and adoption of the variables of the study in the organization surveyed, the research sample was selected intentionally represented by ( 52) of the workers in the existing cement factory, as well as the questionnaire was relied upon as the main tool in collecting data, and the statistical program (SPSS) was adopted in addition to the Excel program) in analyzing and processing the data Most prominent results reached by the researcher were the possession of the existing cement plant vigilance modern technology used in its work as well as the ability of its administrative leaders to monitor the ability surrounding environment enhances it through strategic vigilance. As for the recommendations, they were represented by enhancing commercial vigilance and competitive vigilance, following up on the labor market and customer needs, and focusing on work. Teamwork and gives employees an opportunity to show their creativity, which leads the organization to organizational excellence.